2016
DOI: 10.3109/02713683.2015.1114653
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Changes and Corneal Wound Healing After SMILE and PRK Procedures

Abstract: Using TEM, keratocyte activation could still be observed after SMILE compared to after PRK procedure. Fewer cellular ultrastructural changes were seen after SMILE procedure. Unlike in PRK procedure, no damaged epithelium and endothelium were found after SMILE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 37 publications
0
26
0
1
Order By: Relevance
“…Although both procedures were found to be similar in spherical correction and safety, visual rehabilitation was quicker after SMILE compared to PRK. This could represent a differential healing response between both procedures10. Previous studies investigating astigmatic correction following PRK reported that refractive predictability was worse in PRK for astigmatic treatment compared to spherical correction alone1112.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although both procedures were found to be similar in spherical correction and safety, visual rehabilitation was quicker after SMILE compared to PRK. This could represent a differential healing response between both procedures10. Previous studies investigating astigmatic correction following PRK reported that refractive predictability was worse in PRK for astigmatic treatment compared to spherical correction alone1112.…”
Section: Discussionmentioning
confidence: 98%
“…The amount of energy delivered to the cornea was much lower with femtosecond laser compared to excimer laser25. The main advantage of femtosecond laser compared to excimer laser is its high cutting precision with minimal collateral damage and associated cellular and structural changes10. The response of corneal epithelium may also be different between SMILE and PRK, which required epithelial removal of the treatment zone.…”
Section: Discussionmentioning
confidence: 99%
“…22,29 One possible answer to this question lies in the interface, where tissue removal from an enclosed space causes disarrangements of the stromal collagen Subjective Patient Experience After SMILE and LASIK/Damgaard et al fibrils. 30,31 Clinical studies of LASIK and SMILE have reported significantly higher light scattering up to 6 months after SMILE. 32,33 The initial light scattering and blurring in SMILE may be related to interface irregularities; hence a smooth lenticule dissection is important for the visual outcome 34 together with continuous optimization of the femtosecond laser energy settings.…”
Section: Discussionmentioning
confidence: 99%
“…SMILE generally caused less keratocyte apoptosis, less proliferation, less inflammation, and faster regeneration of nerve density than LASIK and PRK. [31][32][33] Interestingly, keratocyte apoptosis was observed both above and below the flap interface deep in the tissue after LASIK. 31 However, the same was localized to the lenticular interfaces only after SMILE, and the surrounding tissue showed a minimal apoptotic effect in the early phase of wound healing.…”
Section: Discussionmentioning
confidence: 99%